USM INTERNATIONAL STUDENT THRILLS THE JURY WITH TRADITIONAL SONG - MPRC, Pusat Media & Perhubungan Awam (2017)
PENANG, 11 March 2017 Universiti Sains Malaysia (USM) international student from China, Sha Jai Qiang stole the limelight when he clinched second prize at the International 'Irama Malaysia' Concert held recently at Universiti Pendidikan Sultan Idris (UPSI).